2016
DOI: 10.1186/s13071-016-1452-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Leishmania infantum, filariae and Wolbachia spp. in dogs from southern Portugal

Abstract: BackgroundLeishmaniosis caused by the protozoan Leishmania infantum and dirofilariosis caused by the nematodes Dirofilaria immitis or Dirofilaria repens are vector-borne zoonoses widely present in the Mediterranean basin. In addition, some studies reported that the endosymbiont Wolbachia spp. play a role in the biology and pathogenesis of filarial parasites. The aim of this work was to evaluate the frequency of mono- and co-infections by L. infantum, filariae and Wolbachia spp. and their association with clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 25 publications
4
26
0
Order By: Relevance
“…Moreover, in heartworm infected dogs and cats, these bacteria are implemented in pulmonary disease [24,25]. Clarifying these bacteria by antibiotic treatments induces infertility and death of filarioid worms and has reduced the incidence of inflammatory pulmonary lesions and thrombi associated with heartworm disease, providing an effective treatment strategy for the control and eradication of the filarial infection in human and dogs [22,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in heartworm infected dogs and cats, these bacteria are implemented in pulmonary disease [24,25]. Clarifying these bacteria by antibiotic treatments induces infertility and death of filarioid worms and has reduced the incidence of inflammatory pulmonary lesions and thrombi associated with heartworm disease, providing an effective treatment strategy for the control and eradication of the filarial infection in human and dogs [22,26].…”
Section: Discussionmentioning
confidence: 99%
“…These features constitute make its a suitable target for the diagnosis of filarial infection, especially when occurring in dead-end hosts as is the case of D. immitis in humans and cats [24,25]. Recent studies showed that the combined detection of Wolbachia and filarioid DNA improves the diagnosis of these infections [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in vector presence, abundance and activity, as well as increased movements of animals from endemic areas into free territories and vice versa , seem to play key roles in this change in epidemiology [ 16 ]. As a result, the current distribution of CanL and canine heartworm disease (CHD) due to D. immitis is overlapping in several European countries, including Albania [ 17 ], Greece [ 18 ], France [ 2 ], Italy [ 3 ], Portugal [ 13 , 14 ] and Spain [ 19 ]. This means that dogs living in these areas are at risk for both diseases during at least 4–6 months per year on average, which corresponds to the period of activity of the respective vectors (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, epidemiological studies have so far revealed a limited number of cases of co-infection in dogs, with Dirofilaria and Leishmania ( Medkour et al, 2020;Gizzarelli et al, 2019). On the other hand, in dogs co-infected by D. immitis and L. infantum the presence of circulating Wolbachia DNA negatively correlates with clinical signs of leishmaniasis (Maia et al, 2016). We could thus speculate that in dogs infected by the blood-dwelling filaria D. immitis the continuous release of WSP-loaded Wolbachia into the blood stream could modulate the immunity of the host, protecting it from Leishmania infection (even though chronic filarial infections in humans is also associated with macrophage tolerization; e.g.…”
Section: Discussionmentioning
confidence: 99%